2016
DOI: 10.1177/1464884916663597
|View full text |Cite
|
Sign up to set email alerts
|

Reader reaction to news of mass suffering: Assessing the influence of story form and emotional response

Abstract: Drawing from psychological research, the study examines how story form influences reader reaction to news accounts of mass violence in Africa. An online survey with embedded experimental conditions was administered to a US Internet panel (n = 638). Results show that how the story is told affects reader emotional response and, indirectly, charitable giving. Story personification had the strongest influence, followed by stories with photographic images. Use of statistical and mobilizing information had only a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 52 publications
(39 reference statements)
0
26
0
Order By: Relevance
“…Personal stories, involving first person narratives, are more attractive and stimulate empathic responses more efficiently (41)(42)(43). Given that this type of communication seems to be a structural component within the anti-vaccination community, it may be required for users to build strong connections.…”
Section: Towards a Better Communication Strategy For Vaccinationsmentioning
confidence: 99%
“…Personal stories, involving first person narratives, are more attractive and stimulate empathic responses more efficiently (41)(42)(43). Given that this type of communication seems to be a structural component within the anti-vaccination community, it may be required for users to build strong connections.…”
Section: Towards a Better Communication Strategy For Vaccinationsmentioning
confidence: 99%
“…One of the longest running ethical debates in visual journalism is the extent to which news media should run or use graphic images. Research has shown that when audiences feel emotionally connected with news events, they are more likely to change their views or take action (Maier, Slovic, & Mayorga, 2017). To publish violent or graphic imagery is often the way to truthfully and entirely convey a story to the public, without filtering the nature of that story before publication.…”
Section: Propositions For the Influence-network Model Of The Photojoumentioning
confidence: 99%
“…News images give the reader visual information about the story and results in more emotional impulses from the reader. For news to be credible, the reader needs to feel strong and emotional impulses from the news to understand what happened to the victims [66]. Four respondents had a higher image ratio, and these are readers who prefer to receive information from images and pay more attention to them.…”
Section: Discussionmentioning
confidence: 99%
“…Images in the news aim to invoke more significant emotional impulses of respondents and to make it clear whether they feel anxious or not from the news. Based on the experiment by Maier et al [66], there are a few differences bewteen a "straight news story" and "combined photography news." Results showed that news with photos rated significantly higher in credibility.…”
Section: News Selectionmentioning
confidence: 99%